The Role of Amyloid β‐Biomembrane Interactions in the Pathogenesis of Alzheimer's Disease: Insights from Liposomes as Membrane Models. Issue 15 (29th June 2021) - Andrade, Stéphanie; Loureiro, Joana Angélica; Pereira, Maria Carmo
Abstract: The aggregation and deposition of amyloid β (Aβ) peptide onto neuronal cells, with consequent cellular membrane perturbation, are central to the pathogenesis of Alzheimer's disease (AD). Substantial evidence reveals that biological membranes play a key role in this process. Thus, elucidating the mechanisms by which Aβ interacts with biomembranes and becomes neurotoxic is fundamental to developing effective therapies for this devastating progressive disease. However, the structural basis behind such interactions is not fully understood, largely due to the complexity of natural membranes. In this context, lipid biomembrane models provide a simplified way to mimic the characteristics and composition of membranes. Aβ‐biomembrane interactions have been extensively investigated applying artificial membrane models to elucidate the molecular mechanisms underlying the AD pathogenesis. This review summarizes the latest findings on this field using liposomes as biomembrane model, as they are considered the most promising 3D model. The current challenges and future directions are discussed. Abstract : The interactions between amyloid β peptide (Aβ) and biological membranes are significant in the pathogenesis of Alzheimer's disease. If on the one hand, membranes modulate Aβ folding, aggregation, and fibril formation, on the other hand, Aβ disturbs biological membranes. The factors affecting Aβ‐lipid membranes interactions are analyzed, and the current challenges and future directions on this field are discussed.